2022
DOI: 10.3390/su14148279
|View full text |Cite
|
Sign up to set email alerts
|

Optimising Changeover through Lean-Manufacturing Principles: A Case Study in a Food Factory

Abstract: Operations management is a key aspect in any manufacturing business. Optimising the management of manufacturing operations allows improvement of the productivity and efficiency of industrial activities. To achieve this, reducing waste from manufacturing processes and, therefore, implementing lean-manufacturing principles, is key. This article presents a case study to reduce waste in changeover processes at a ready-meal manufacturer based in South Yorkshire, UK. We identified a large number of activities as par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…The study by Kolla, Minuferkr, and Plapper (2019) [49] shows that the combination of SMED "kaizen" and "heijunka" can help in SME product customization. As shown in a case study [50], in a food factory with the implementation of SMED, it was possible to achieve a 70% improvement in the overall OEE indicator. Digital tools, e.g., simulation software and 3D printing, can prototype and avoid the risk of product failure.…”
Section: Lean Manufacturing and Lean-greenmentioning
confidence: 93%
“…The study by Kolla, Minuferkr, and Plapper (2019) [49] shows that the combination of SMED "kaizen" and "heijunka" can help in SME product customization. As shown in a case study [50], in a food factory with the implementation of SMED, it was possible to achieve a 70% improvement in the overall OEE indicator. Digital tools, e.g., simulation software and 3D printing, can prototype and avoid the risk of product failure.…”
Section: Lean Manufacturing and Lean-greenmentioning
confidence: 93%
“…The only cases are those described by Roriz et al. (2017) for a company in the paper industry and Gargia-Gargia et al. (2022) in the food industries.…”
Section: State Of the Artmentioning
confidence: 99%
“…, 2020). Other link a high degree of Lean tool implementation with higher production performance within companies (Losonci and Demeter, 2013; Sahoo and Yadav, 2018), and yet other studies have reported the effects of specific Lean tools on the production system (Garcia-Garcia et al. , 2022; Shahriar et al.…”
Section: Overview Of Research Contextmentioning
confidence: 99%
“…Several studies on the growing use of Lean tools in industry (Bonavia and Marin, 2006;Jezierski and Janerka, 2013;Singh and Kumar, 2021) link Lean tool use to higher business performance (Shah and Ward, 2003;Olhager and Prajogo, 2012;Belekoukias et al, 2014;Hernandez-Matias et al, 2020). Other link a high degree of Lean tool implementation with higher production performance within companies (Losonci and Demeter, 2013;Sahoo and Yadav, 2018), and yet other studies have reported the effects of specific Lean tools on the production system (Garcia-Garcia et al, 2022;Shahriar et al, 2022;Gebeyehu et al, 2022). Other research includes longitudinal studies on the growing use of Lean tools in manufacturing companies (Piercy and Rich, 2015;Rajagopalan and Solaimani, 2020 Lean tools in Spanish manufacturing firms Rajagopalan, 2020).…”
Section: Classification Of Lean Toolsmentioning
confidence: 99%